H-shaped oxalate-bridging lanthanoid-incorporated arsenotungstates. Issue 44 (4th November 2020) - Chen, Hanhan; Xiao, Zikang; Yan, Bing; Wu, Hechen; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract : A series of oxalate-bridging di-Ln 3+ -incorporated H-shaped polyoxometalates were synthesized and their stability in solution was evidenced by Raman spectroscopy. Abstract : Three oxalate-bridging lanthanide-based polyoxometalates (Ln-POMs) K17 Na2 H5 [{(As2 W19 O67 (H2 O))Ln(H2 O)2 }2 (C2 O4 )]·50H2 O. [Ln = Sm 3+ (1 ), Pr 3+ (2 ), and Ce 3+ (3 )] were successfully synthesized. The structures were further characterized by single-crystal X-ray diffraction analyses, Raman spectroscopy, elemental analyses, powder X-ray diffraction (PXRD), IR spectra, UV/vis diffuse reflectance spectroscopy, and thermogravimetric analysis (TGA). The structural characterization study reveals that Ln-POMs 1–3 crystallize in the form of the triclinic space group P 1̄ and consist of an oxalate bridging di-Ln 3+ -incorporated H-shaped dimer, which can also be viewed as a combination of two half-units {Ln(As2 W19 O67 (H2 O))(H2 O)2 }2 22− related by an inversion center. It is worth noting that the opening angle (33.01°) from the [As2 W19 O67 (H2 O)] 14− fragment in 1–3 is less than that of the [As2 W19 O67 (H2 O)] 14− precursor (40.99°). Furthermore, the stability of 1–3 in aqueous solution and their solid-state photoluminescence properties have also been investigated in this work.